Valor percebido do cliente: um estudo sobre o relacionamento entre as instituições de ensino superior e seus alunos - Reichelt, Valesca Persch (2007)
This thesis proposal is to give a contribution to Perceived Value studies, in the context of relationship marketing, focusing the research in the relation among higher education institutions and their students. Data were collected with Rio Grande do Sul higher education institutions’ students taking degree in Business Administration, in three phases. In the first phase, qualitative and exploratory research were conducted, with ten in depth interviews with students. Then a sample of 133 respondents was collected, for validation and purification of the measurement scales. In the third phase, 569 questionnaires were collected for the final sample, which allowed the structural models tests relating the following subjects: Perceived Value, Satisfaction, Relational Satisfaction and Loyalty. Discussions about these subjects are presented in the literature review, which also presents a conceptual model integrating them and thirteen hypotheses of causal relations among constructs. Using Structural Equations Modeling, the hypotheses are tested and a structural model is proposed, with adequate adjust indexes. The relations highlighted in the model show that the predictors of Perceived Value are Perceived Quality, Behavioral Price, Monetary Price, Reputation and Emotional Response. Monetary Price is the construct which more influenced the Perceived Value, followed by Reputation, indicating that higher education institutions should concern about image and status. Perceived Value demonstrated heavy influence on Satisfaction. Another Satisfaction predictor was Relational Satisfaction, showing that Relationship Marketing actions are important in continuous service companies, as such in the education sector. Loyalty antecedents in the model are Satisfaction, Perceived Value and Relational Satisfaction, being the last two more influent than Satisfaction. The conclusions highlight the importance of creating value to customers and establishing satisfactory relational ties with them. Last but not least, suggestions to following researches are given.